Dragging up the past: investigating historical representations of drag in South Africa. (29th December 2016) - McCormick, T.
Abstract : Drag performances at bars, clubs, pageants and shebeens are wildly popular in South Africa. This can be gauged by the number of websites and posts on various media platforms. However, despite these popular cultural manifestations of drag, academic interest in theorising drag is limited. In this article I attempt to ignite academic interest in theorising drag in the South African context. The reason why I use the term 'ignite' is that after an extensive data base search I only found four published articles on drag, the last of which was published in 2004. In addition, no South African gay and lesbian non-fiction book has included a discussion of drag since Defiant Desire: Gay and Lesbian Lives in South Africa (1994), edited by Gevisser and Cameron. The five chapters on drag in Defiant Desire have been used by the researchers above to corroborate or illustrate their arguments about drag in South Africa but have never before been the object of an academic investigation. In this article I 'drag up the past' by foregrounding the five chapters on drag from Defiant Desire and I investigate in particular how the language used by the various writers positions the role and place of the drag queen in political and personal political discourses of the time.